Tinjauan Hukum Islam Terhadap Tindak Pidana Pungutan Liar Dalam Bisnis Pariwisata Di Sumatera Utara - Mhd. Hafiz Fahrezy Yopi; M. Iqbal, Lc., M.Ag. (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research examines the crime of extortion in the tourism business in North Sumatra from an Islamic legal perspective. Extortion has become a detrimental problem for the tourism sector due to the practice of illegal levies carried out by certain individuals, including entrance fees without official tickets, illegal parking fees, and administrative fees without permits. This practice not only damages the comfort of tourists and the image of tourist destinations but also hinders regional economic growth. In Indonesian positive law, extortion is regulatedas a criminal act of corruption with strict criminal sanctions. However, weak law enforcement makes this practice difficult to eradicate. From an Islamic legal perspective, extortion is an evil act and a major sin because it takes the rights of others unlawfully and violates the principles of justice, honesty, and trustworthiness. This research uses a qualitative descriptive method with a literature review, collecting and analyzing data from various sources, such as books, journals, and articles, without direct fieldwork. The aim is to gain a deeper understanding of the topic based on relevant written sources. Efforts to eradicate extortion in North Sumatra tourism must be carried out comprehensively with synergy between the government, religious leaders, business actors, and the community. Strict law enforcement, tariff transparency, strict supervision, and the implementation of e government are the main strategies. In addition, moral education and community empowerment based on Islamic values can strengthen a clean and just tourism culture. With these steps, it is hoped that the tourism sector in North Sumatra can develop more healthily and sustainably, providing optimal benefits to the community and the nation.